2016
DOI: 10.1136/rmdopen-2016-000349
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous destructive periodontitis and skeletal bone damage in transgenic mice carrying a human shared epitope-codingHLA-DRB1allele

Abstract: ObjectiveShared epitope (SE)-coding DRB1 alleles are associated with bone erosion in several diseases, including rheumatoid arthritis (RA) and periodontal disease (PD), but the underlying mechanism is unknown. We have recently identified the SE as an osteoclast-activating ligand. To better understand the biological effects of the SE in vivo, here we sought to determine whether it can facilitate spontaneous bone damage in naïve mice.Methods3-month old naïve transgenic mice that carry the human SE-coding allele … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…It is possible that some common genetic traits are associated with increased susceptibility to these conditions. One potential genetic influence connecting RA and PD is the shared epitope (SE)-coding HLA-DRB1 allele [112]. According to van der Woude et al [113] 50% of the risk to develop RA is attributed to genetic factors, and the most relevant genetic association in RA is with the SE-coding HLA-DRB1 gene that confers more than 80% of susceptibility for joint destruction [64,114].…”
Section: Mechanistic Studies Linking Ra and Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that some common genetic traits are associated with increased susceptibility to these conditions. One potential genetic influence connecting RA and PD is the shared epitope (SE)-coding HLA-DRB1 allele [112]. According to van der Woude et al [113] 50% of the risk to develop RA is attributed to genetic factors, and the most relevant genetic association in RA is with the SE-coding HLA-DRB1 gene that confers more than 80% of susceptibility for joint destruction [64,114].…”
Section: Mechanistic Studies Linking Ra and Pdmentioning
confidence: 99%
“…The SE-coding DRB1 alleles have been associated with bone erosions in RA as well as alveolar bone destruction during PD progression [118,119,120]. Recent data [112] shows that the transgenic mice carrying a human SE-coding HLA-DRB1 allele present spontaneous alveolar bone resorption and osteopenic skeletal changes, characterized by slenderer tibiae and decreased total bone area in the marrow and cortical tibial bones. Furthermore, overexpression of pro-inflammatory cytokines IL-17 and TNF-α were also found in SE-positive mice.…”
Section: Mechanistic Studies Linking Ra and Pdmentioning
confidence: 99%
“…The possible role of SE-coding DRB1 alleles has been recently underlined by Gehlot and colleagues: the authors observed that transgenic SE+ mice, but not SE- mice, spontaneously developed PD, associated with IL17 overexpression and periostin disruption. Moreover, SE-positive mice showed significantly lower mandibular bone volumetric and mineralization parameters, together with increased alveolar bone resorption [34].…”
Section: Introductionmentioning
confidence: 99%
“…Data from literature provides some evidences to support the association between an aggressive PD and SNPs in interleukin 1 beta (IL1 β ), interleukin 1 receptor antagonist (IL1RN), FCGR IIIb, vitamin D receptor (VDR), and Toll-like receptor 4 (TLR4) genes. Moreover, a chronic PD was associated with polymorphisms in IL1B, IL1RN, IL6, IL10, VDR, CD14, TLR4, and matrix metalloproteinase-1 (MMP1) genes [34]. The low statistical power of these studies was also demonstrated by the results of the meta-analysis conducted by Nikolopoulos and colleagues in 2008, confirming exclusively a moderate and weak positive association between the IL1 composite and IL1B-511 genotypes and the occurrence of chronic PD [36].…”
Section: Introductionmentioning
confidence: 99%
“…SE-coding HLA-DRB1 alleles have also been found to associate with type 1 diabetes, autoimmune hepatitis, polymyalgia rheumatica, and temporal arteritis 11,12,13,14 , among other conditions. Additionally, the SE has been found to be a risk factor for erosive bone damage in nosologically-distinct conditions, such as periodontal disease, systemic lupus erythematosus and psoriatic arthritis 15,16,17,18,19 .…”
Section: Introductionmentioning
confidence: 99%